Displacement and Von Mises stress analysis in hydraulic actuator cylinder materials for military vehicle applications - Massuradi Simbolon; Asrori Asrori; Satworo Adiwidodo; Sugeng Hadi Susilo (Politeknik Negeri Lhokseumawe, 2026)
Material selection is crucial for ensuring the structural reliability of hydraulic actuator cylinders operating under high-pressure and dynamic loading conditions. Conventional methods, which focus on cost or manufacturing ease, may neglect detailed performance analysis, leading to local stress concentrations exceeding material strength. This research addresses this issue by comparing the performance of AISI 1020, AISI 1035, and AISI A2 tool steel using Finite Element Analysis (FEA) and conducting experimental testing to assess displacement, Von Mises stress distribution, and safety factor under various loads (450 N, 900 N, and 1350 N). The experimental results show that AISI A2 performed best in structural response with the highest safety margin, AISI 1035 exhibited the highest stress, and AISI 1020 exhibited the highest displacement. In FEA, AISI A2 showed a controlled maximum displacement of 0.28 mm with a safety factor of 3.94, compared with AISI 1020, which reached 0.82 mm and a safety factor of 1.23. The findings support the significant influence of material mechanical properties on actuator structural integrity and confirm that AISI A2 provides the highest resistance to deformation and stress concentration. The study demonstrates the effectiveness of FEA in optimizing actuator material selection for high-load applications.